Entrenamiento Para El Teatro Callejero (2016)
This thesis is a research that aims to demonstrate training for the street theater based on the experiences of some long-time teachers, this phenomenon arises from interest in the study of acting pedagogy, in investigating certain imaginaries and phenomena that occur today in the artistic field. As an artist-pedagogue in training, I undertake this research in order to contribute with some material for the study of actors, actresses, students and people who want to venture into this wonderful world of street theater